Mendorong Efisiensi Perdagangan Global dengan Implementasi WTO Trade Facilitation Agreement di Indonesia - Grevicra De Rosario Sihotang (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
The implementation of the Trade Facilitation Agreement (TFA) adopted by the World Trade Organization (WTO) since 2017 aims to reduce administrative barriers in international trade and improve the efficiency of the export-import process. By ratifying the TFA through Law No. 17/2017, Indonesia is expected to optimize trade and customs procedures, speed up the movement of goods, and reduce trade costs, which in turn supports economic growth and exports. The TFA includes simplification, modernization, and harmonization of export-import procedures, which are expected to provide significant benefits, especially for developing countries such as Indonesia. This research aims to analyze the implementation of trade facilitation in Indonesia. The research method used is normative legal research, which examines legal data sourced from literature (secondary legal materials). The implementation of this agreement has shown positive impacts, including reduced trade costs and increased export access, especially for small and medium enterprises. The Indonesian government, through the ratification of the TFA, aims to facilitate global trade by increasing transparency and efficiency in the export-import mechanism.